Marketing Travel & Leisure Services - Moschis G.P. (2023)
Older Americans are becoming increasingly active as consumers of a wide variety of travel and leisure-related services. The recent COVID-19 pandemic and terrorist activities notwithstanding, the long-term prospects for the travel and leisure industry are favorable as it applies to the older consumer market. Conflicting factors such as higher life expectancy, increased ability to travel due to higher income levels, but more health and social constraints mean that there will be more diverse travel and leisure demands from older travellers. It is likely that it will be increasingly necessary for businesses to create travel opportunities and services for every budget to satisfy the diverse travel needs and take advantage of this booming market. This chapter uses existing knowledge that has implications for developing strategies and tactics to effectively market travel and leisure services to older consumers; it offers in a condensed format recommendation for marketing strategies (segmentation, target selection and positioning), as well as programs/tactics (product development, promotion, pricing and distribution) for travel and leisure services in general, as well as for four types of services: Lodging, cruise lines, air lines, and casino gambling.